Kinetic Resolution of Tertiary Benzyl Alcohols via Palladium/Chiral Norbornene Cooperative Catalysis - Hua, Yu; Liu, Ze‐Shui; Xie, Pei‐Pei; Ding, Bo; Cheng, Hong‐Gang; Hong, Xin; Zhou, Qianghui (Angewandte Chemie International Edition, 2021)
Herein we report a highly enantioselective kinetic resolution of tertiary benzyl alcohols via palladium/chiral norbornene cooperative catalysis. With simple aryl iodides as the resolution reagent, a wide range of readily available racemic tertiary benzyl alcohols are applicable to this method. Both chiral tertiary benzyl alcohols and benzo[c]chromene products are obtained in good to excellent enantioselectivities (selectivity factor up to 544). The appealing synthetic utility of the obtained enantioenriched tertiary alcohols is demonstrated by the facile preparation of several valuable chiral heterocycles. Preliminary mechanism studies include DFT calculations to explain the origin of enantiodiscrimination and control experiments to uncover the formation of a transient axial chirality during the kinetic resolution step. A highly enantioselective kinetic resolution of tertiary benzyl alcohols via palladium/chiral norbornene cooperative catalysis is developed. Simple aryl iodides are used as the resolution reagent. Both enantioenriched tertiary benzyl alcohols and benzo[c]chromene products are obtained in good to excellent enantioselectivities. The synthetic applications are demonstrated by the facile synthesis of diversified biorelevant heterocycles.